Functional improvement of monitoring the dynamic characteristics of information andcommunication networks - Бабич, Юрий Олегович; Никитюк, Леся Андреевна (Eastern-European Journal of Enterprise Technologies, 2015)
The study reveals conceptual principles of predictive monitoring of the dynamic characteristics of modern information and communication networks. The suggested procedures of predictive monitoring are aimed at a functional improvement of the existing types of monitoring information and communication networks. The procedures that include consecutive stages of short-term, situational and long-term prognostication are implemented by means of statistic analysis and aimed at an early detection of possible emergencies. The paper suggests asystem of predictive monitoring. The existing types of monitoring that are functionally improved by means of the procedures of predictive monitoring are illustrated in terms of TMNand TINA. Predictive monitoring allows making timely decisions on reconfiguring the resources of the monitored objectin order to either prevent emergencies or decide on the network reconstruction if the means of reconfiguration are no more effective.